Jumping Conlusion Tafsir: Penyimpangan Ayat-Ayat Khilafah HTI dalam Kitab Daulah Islamiyyah - Lufaefi, Lufaefi (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2019)
Al-Quran is a revelation that explains all problems. This includes the issue of leadership (khil?fah). Regardless of the form of the khil?fah in the Koran, it is certain that there is no doubt that the khil?fah was the spotlight of the divine kalam. Because any problem must be mentioned in the Koran. However, what if the interpretation of the verse is diverted to something that does not mean the verse itself? Through the approach to content and context analysis, in the Daulah Islamiyyah book found verses of the Koran which were interpreted by jumping conclusions, such as QS. Al-M?'idah [5]: 48 and QS. Al-M?'idah [5]: 49. These verses clearly do not discuss khil?fah, but are interpreted by Taqiyuddin an-Nabhani to come to the conclusion as obligatory to establish an Islamic State institution (khil?fah isl?miyyah). Such interpretation is far from what the verse wants to say, even worth politicizing the verses of the Koran.